Lifelong learning in a learning society: are community learning centres the vehicle? - Ahmed, Manzoor (© 2014 Brill, 2016)
This book chapter was published in Education, Learning, Training: Critical Issues for Development [ © 2014 Graduate Institute of International and Development Studies ] and the definite version is available at: http://doi.org/10.1163/9789004281158_007. The book website is at: http://booksandjournals.brillonline.com/content/books/b9789004281158_007